Risk of severe COVID-19 outcomes associated with rheumatoid arthritis and phenotypic subgroups: a retrospective, comparative, multicentre cohort study. (November 2022) - Figueroa-Parra, Gabriel; Gilbert, Emily L; Valenzuela-Almada, Maria O; Vallejo, Sebastian; Neville, Matthew R; Patel, Naomi J; Cook, Claire; Fu, Xiaoqing; Hagi, Ramla; McDermott, Gregory C; Dilorio, Michael A; Masto, Lucy; et al.
Summary: Background: Rheumatoid arthritis has been associated with severe COVID-19, but few studies have investigated how phenotypes of rheumatoid arthritis affect these associations. We aimed to investigate the associations between rheumatoid arthritis and phenotypes of interstitial lung disease, serostatus, and bone erosions with COVID-19 severity. Methods: We did a retrospective, comparative, multicentre cohort study at two large health-care systems (Mayo Clinic [19 hospitals and affiliated outpatient centres] and Mass General Brigham [14 hospitals and affiliated outpatient centres]) in the USA. Consecutive patients with rheumatoid arthritis meeting the 2010 American College of Rheumatology/European League Against Rheumatism classification criteria and who had COVID-19 between March 1, 2020, and June 6, 2021, were matched 1:5 on age, sex, and calendar date with patients without rheumatoid arthritis (comparators). Data were received from electronic health records from Mayo Clinic and Mass General Brigham. We examined subgroups of patients with rheumatoid arthritis by phenotypic features: rheumatoid arthritis-associated interstitial lung disease, seropositivity (for anti-cyclic citrullinated peptide, rheumatoid factor, or both), and bone erosions. Severe COVID-19 was a composite of hospitalisation or death. We used Cox regression to estimate hazard ratios (HR) for severe COVID-19, comparing rheumatoid arthritis and subgroups to the comparator group. Findings: We identified 582 patients with rheumatoid arthritis and 2875 matched comparators, all of whom had COVID-19 within the study dates. The mean age of those with rheumatoid arthritis was 62 [SD 14] years, 421 (72%) of 582 were women and 161 (28%) were men, 457 (79%) were White, 65 (11%) were Hispanic or Latino, and 41 (7%) were Black. Among patients with rheumatoid arthritis, 50 (9%) of 582 had interstitial lung disease, 388 (68%) of 568 were seropositive, and 159 (27%) of 582 had bone erosions. Severe COVID-19 occurred in 126 (22%) of 582 patients with rheumatoid arthritis versus 363 (13%) 2875 in the comparator group. Patients with rheumatoid arthritis had an HR of 1·75 (95% CI 1·45–2·10) for severe COVID-19 versus the comparator group. Patients with rheumatoid arthritis-associated interstitial lung disease had an HR of 2·50 (1·66–3·77) versus the comparator group for severe COVID-19. The risk for severe COVID-19 was also higher in patients with rheumatoid arthritis who were seropositive (HR 1·97 [95% CI 1·58–2·46]) or had erosive disease (1·93 [1·41–2·63]) than for those in the comparator group. Interpretation: Patients with rheumatoid arthritis have an increased risk of severe COVID-19 across phenotypic subgroups, especially among patients with interstitial lung disease. These findings suggest that rheumatoid arthritis with interstitial lung disease, or its treatment, might be a substantial contributor to severe COVID-19 outcomes for patients with rheumatoid arthritis. Funding: None.